Multiscale Multimodal Investigation of the Intratissural Biodistribution of Iron Nanotherapeutics with Single Cell Resolution Reveals Co‐Localization with Endogenous Iron in Splenic Macrophages. Issue 2 (26th December 2022) - Balfourier, Alice; Tsolaki, Elena; Heeb, Laura; Starsich, Fabian H. L.; Klose, Daniel; Boss, Andreas; Gupta, Anurag; Gogos, Alexander; Herrmann, Inge K.
Abstract: Imaging of iron‐based nanoparticles (NPs) remains challenging because of the presence of endogenous iron in tissues that is difficult to distinguish from exogenous iron originating from the NPs. Here, an analytical cascade for characterizing the biodistribution of biomedically relevant iron‐based NPs from the organ scale to the cellular and subcellular scales is introduced. The biodistribution on an organ level is assessed by elemental analysis and quantification of magnetic iron by electron paramagnetic resonance, which allowed differentiation of exogenous and endogenous iron. Complementary to these bulk analysis techniques, correlative whole‐slide optical and electron microscopy provided spatially resolved insight into the biodistribution of endo‐ and exogenous iron accumulation in macrophages, with single‐cell and single‐particle resolution, revealing coaccumulation of iron NPs with endogenous iron in splenic macrophages. Subsequent transmission electron microscopy revealed two types of morphologically distinct iron‐containing structures (exogenous nanoparticles and endogenous ferritin) within membrane‐bound vesicles in the cytoplasm, hinting at an attempt of splenic macrophages to extract and recycle iron from exogenous nanoparticles. Overall, this strategy enables the distinction of endo‐ and exogenous iron across scales (from cm to nm, based on the analysis of thousands of cells) and illustrates distribution on organ, cell, and organelle levels. Abstract : The biological fate of (iron) nanotherapeutics is of high interest, however, it is challenging to assess due to the high endogenous iron background in mammalian tissues. This article reports a methods cascade enabling the localization of iron nanotherapeutics across scales from the organ to the organelle level and enables distinction between exogenous and endogenous (ferritin) iron deposits based on correlative spectromicroscopy.